The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s41155-019-0132-5
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and job dissatisfaction with health work

Abstract: Objective The purpose of this study is to evaluate the association between psychosocial aspects at work and dissatisfaction among health workers in five cities in Bahia, Brazil. Methods The evaluation was based on different models proposed to measuring occupational stress and possible combinations between them: demand-control model (DCM) and effort-reward imbalance (ERI). We conducted a cross-sectional epidemiological study including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
7
0
3
Order By: Relevance
“…Effort-reward imbalance is characterized by a recurring lack of reciprocity between the efforts expended at work and the rewards—both direct and indirect—received in return ( 23 ). In similar fields with similar demands, i.e., human health care, high levels of occupational stress and effort-reward imbalances have been noted with job dissatisfaction rates reported of up to 1 in every 4 workers ( 24 , 25 ). In addition to mental health effects, chronic work stress can contribute to increased risks for coronary heart disease ( 23 ).…”
Section: Factors Contributing To Workplace Stress In Animal Research mentioning
confidence: 99%
“…Effort-reward imbalance is characterized by a recurring lack of reciprocity between the efforts expended at work and the rewards—both direct and indirect—received in return ( 23 ). In similar fields with similar demands, i.e., human health care, high levels of occupational stress and effort-reward imbalances have been noted with job dissatisfaction rates reported of up to 1 in every 4 workers ( 24 , 25 ). In addition to mental health effects, chronic work stress can contribute to increased risks for coronary heart disease ( 23 ).…”
Section: Factors Contributing To Workplace Stress In Animal Research mentioning
confidence: 99%
“…Independent of these differences, several occupational studies demonstrated the importance of working conditions for health [ 7 , 9 , 11 ]. Brazilian studies with the working population demonstrated an association between job strain and cardiovascular risk [ 36 ], metabolic syndrome [ 37 ], migraine [ 38 ], poor quality of life [ 39 ], poor self-rated health [ 40 ], job dissatisfaction [ 41 ], and sickness-absenteeism from the job [ 42 ]. Our study also adds to the knowledge about working and health conditions since low decision authority at work, and low skill discretion were related to obesity and poor self-rated health.…”
Section: Discussionmentioning
confidence: 99%
“…A insatisfação com o trabalho mediou o efeito dos aspectos psicossociais e da SAP na ocorrência de TMC. Os resultados encontrados corroboram o conhecimento descrito na literatura: o impacto negativo da insatisfação com o trabalho na saúde mental 1,2,3,7 ; a repercussão do estresse ocupacional na insatisfação com o trabalho 1,32,33 ; bem como a associação entre estressores ocupacionais e TMC 12 . Também fortalecem as duas hipóteses de trabalho investigadas: (1) associação entre a insatisfação e transtornos mentais (a insatisfação contribui diretamente para a ocorrência de TMC); (2) os aspectos psicossociais do trabalho (estressores e protetores) e a SAP podem associar-se positiva ou negativamente tanto à insatisfação quanto aos transtornos mentais, modificando a relação entre a insatisfação com o trabalho e os TMC.…”
Section: Discussionunclassified
“…A variável latente AE esteve associada positivamente à insatisfação e aos TMC, confirmando a nocividade das dimensões deste construto (elevados níveis de demanda psicológica, demanda física, esforço e comprometimento excessivo com o trabalho) sobre os níveis de satisfação laboral e também sobre a saúde mental dos/as trabalhadores/as. Estudos prévios observaram que as demandas físicas e psicológicas do trabalho, variáveis indicadoras do construto AE, quando elevadas, contribuem para o aumento do estresse ocupacional com repercussão nos níveis de satisfação com o trabalho 1,33 O esforço refere-se à resposta do indivíduo às demandas que lhe são apresentadas. Quando o esforço com o trabalho não é recompensado adequadamente, contribui para elevar o grau de insatisfação com o trabalho.…”
Section: Modelo Estrutural Coeficientes Padronizadosunclassified